Response of square honeycomb core sandwich panels to granular matter impact. (July 2018) - Kyner, Anne; Dharmasena, Kumar; Williams, Keith; Deshpande, Vikram; Wadley, Haydn
Highlights: The out of plane displacement of edge restrained, grade 304 stainless steel sandwich panels has been measured after impact by rapidly expanding spherical shells of water saturated granular media at various velocities. The radial expansion of the spherical shells was imaged using high-speed video techniques and the radial velocity shown to vary from 500 to1200 m/s. The impact pressure and transmitted impulse were also measured using a Kolsky bar positioned at a symmetric location to the panel center. Discrete particle-based simulations successfully predicted particle front positions, velocities, impact pressures and plate deformations. The study has confirmed recent predictions that the panels out of plane displacement would be less than that of an equivalent solid plate provided the deflection did not exceed the panel thickness. Abstract: The deformation of square honeycomb core, stainless steel sandwich panels by the impact of explosively accelerated granular matter has been investigated and compared to results from a previous study using equivalent (same material and mass per unit area) solid plates subjected to similar impulsive loadings. Spherical explosive charges surrounded by 25–150 kg mass annular shells of water-saturated granular media (either fused silica or zirconia particles) were suspended above the center of the edge clamped test panels. The radially expanding granular particle front velocities were measured from high-speed video images, and revealed that the granular matter had been accelerated to velocities of 500–1200 m/s after detonation. A Kolsky bar was used to measure the time-dependent pressure and impulse at a position equivalent to the panel center, while the permanent deflections of the sandwich panels were determined by profilometry after the experiments. Even though fracture of electron beam welds used to attach the back face sheet to the sandwich panel core occurred in all the tests, the permanent deflections of the sandwich panel back faces were significantly less than those of equivalent solid plates, and were accompanied by minimal core compression. Discrete particle simulations of the granular matter acceleration and impact loading of the sandwich panels indicated that their superior deflection benefit arose from their high bending resistance rather than particle-structure interactions. This benefit was offset when the rear face of the sandwich was kept the same distance from the impulsive source as that of the solid plate since the impact face of the sandwich panel was closer to the impulsive source, subjecting it to a higher impulse than the solid plate. However, a substantial deflection reduction was still achieved by use of a strong core sandwich design.